A method for preparing nickel cobalt hydroxide nanosheets and prepared nickel cobalt hydroxide nanosheets
By forming Co-ZIF nanosheets on nickel foam and reacting with nickel salt ion ion exchange reaction, hollow triangular nickel-cobalt hydroxide nanosheets were prepared, which solved the problem of high cost of precious metal catalysts and low activity of traditional NiCo catalysts, and achieved high efficiency , stable electrocatalytic performance and environmentally friendly preparation process.
Patent Information
- Application Number
- CN202111435898.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-11-26
AI Technical Summary
The existing precious metal-based electrocatalysts have low catalytic activity and high cost in anode reaction (OER), which is difficult to apply on a large scale, and the traditional NiCo hydroxide catalyst preparation method is poor in environmental friendliness and takes a long time.
Co-ZIF nanosheets were formed on foam nickel foam by 2-methylimidazole and cobalt salt. Hollow triangular nickel-cobalt hydroxide nanosheets were prepared by ion exchange reaction with nickel salt in ethanol, and their high specific surface area was used and The roughness exposes more active sites, regulating the electronic structure to improve electrocatalytic performance.
The prepared hollow triangular nickel-cobalt hydroxide nanosheets exhibit excellent catalytic performance and stability in OER, significantly improving the kinetics of the anode reaction, with great potential to replace precious metal catalysts, and the preparation process is simple and environmentally friendly.
Smart Images

Figure CN114108005B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of double metal hydroxide nanomaterials, and in particular to a method for preparing a hollow triangular nickel-cobalt hydroxide nanosheet and the nickel-cobalt hydroxide nanosheet prepared by the method. Background Art
[0002] With the rapid development of society, energy crisis and climate change are becoming increasingly serious, prompting people to explore sustainable clean energy. Electrocatalytic water splitting is considered to be the most promising strategy to achieve clean and sustainable energy, but it is hindered by the slow kinetics of the anode reaction - oxygen evolution reaction (OER). Therefore, it is necessary to explore efficient and low-cost catalysts to better improve the OER activity.
[0003] At present, commonly used OER electrocatalysts are precious metal (Pt, Ir, Ru, etc.) based catalysts, but the small reserves and high prices of precious metals further hinder their large-scale application. Therefore, it is urgent to develop efficient, low-cost, and highly stable catalysts to replace precious metal-based catalysts. Transition metals, transition metal oxides, and transition metal hydroxides are expected to become catalysts to replace OER precious metals due to their low cost, good stability, and easy preparation. Among them, NiCo hydroxide has attracted great attention due to its adjustable structure and simple synthesis. Although NiCo double hydroxide electrocatalysts have made great progress, they still face the problems of poor conductivity and low catalytic activity in OER. Therefore, it is crucial to optimize NiCo double hydroxide electrocatalysts to improve OER performance. Invention patent application CN 111921529A discloses a method for preparing a nickel-cobalt metal organic framework / nickel-cobalt metal hydroxide heterogeneous material, which is obtained by using urea, nickel salt, cobalt salt, terephthalic acid, N,N-dimethylformamide, etc., and then through a reactor and centrifugation to obtain a nickel-cobalt metal organic framework / nickel-cobalt metal hydroxide heterogeneous material. This method is less environmentally friendly. Invention patent application CN 112299494 A discloses a method for preparing a nickel-cobalt hydroxide material, which is prepared by using nickel salt, cobalt salt, sodium hydroxide, ammonia water, etc., through coprecipitation and long-term reaction. The preparation method of the catalyst uses a strong base, and the reaction generally requires heating for dozens of hours, which is time-consuming. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing nickel cobalt hydroxide nanosheets, which is simple, convenient and environmentally friendly. The prepared nickel cobalt hydroxide nanosheets have abundant active sites, good OER catalytic performance and high stability.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] A method for preparing nickel cobalt hydroxide nanosheets comprises the following steps:
[0007] (a) 2-methylimidazole and cobalt salt are dissolved in water to obtain solutions, the two solutions are mixed and added into nickel foam, and the mixture is taken out after stirring to obtain Co-ZIF nanosheets supported on nickel foam, wherein the loading amount of the Co-ZIF nanosheets on the nickel foam is 5 to 10 mg cm -2 ;
[0008] (b) Mixing the Co-ZIF nanosheets supported on nickel foam and nickel salt in ethanol, stirring at a constant temperature of 20-80° C. for 1-10 hours, and taking out to obtain nickel cobalt hydroxide nanosheets supported on nickel foam, wherein the molar ratio of the cobalt salt to the nickel salt is 1:1-10.
[0009] Preferably, the cobalt salt is selected from Co(NO3)2·6H2O, CoCl2·6H2O, Co(NO3)2 or C4H6CoO4·4H2O; the nickel salt is selected from Ni(NO3)2·6H2O, Ni(NO3)2, NiSO4 or NiCl2.
[0010] Preferably, the loading amount of the Co-ZIF nanosheets on the nickel foam is 6-7 mg·cm -2 ; The molar ratio of the cobalt salt to the nickel salt is 1:7-8.
[0011] Preferably, the Co-ZIF nanosheets supported on the nickel foam are obtained after continuous stirring for 3 hours in the step (a); the Co-ZIF nanosheets supported on the nickel foam and the nickel salt are mixed in ethanol, and stirred at a constant temperature of 27° C. for 1 to 2 hours to obtain the nickel cobalt hydroxide nanosheets supported on the nickel foam.
[0012] The present invention also provides a nickel cobalt hydroxide nanosheet prepared by the method, wherein the nickel cobalt hydroxide nanosheet is a hollow triangular structure.
[0013] In the above preparation method, nickel foam is used as a substrate, and a Co-ZIF (ZIF refers to a zeolite imidazole ester skeleton structure compound) triangular nanosheet array is prepared instead of nanoparticles through the coordination reaction of cobalt ions and 2-methylimidazole. Then, Co-ZIF is used as a template, and an ion exchange reaction is carried out with a nickel salt in ethanol to obtain a hollow triangular nickel cobalt hydroxide nanosheet composed of nanosheets. The prepared catalyst has a high specific surface area and roughness, which is conducive to the exposure of more active sites during the catalytic reaction. At the same time, the hollow structure is conducive to improving the mass transfer efficiency of the reactants, and the ordered array structure can provide a channel for the discharge of oxygen bubbles. In addition, the incorporation of nickel can effectively adjust the electronic structure of the material, thereby obtaining excellent electrocatalytic performance. The hollow triangular nickel cobalt hydroxide nanosheet catalyst prepared by the above method does not require any binder, has good catalytic performance in OER, is highly stable, can significantly improve the kinetics of OER, and thus helps to overcome the bottleneck of the slow kinetics of the anode oxygen evolution reaction of electrolyzed water. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a SEM spectrum of the hollow triangular nickel-cobalt hydroxide nanosheets prepared in Example 1;
[0015] Figure 2 is a TEM spectrum of the hollow triangular nickel-cobalt hydroxide nanosheets prepared in Example 1;
[0016] Figure 3 This is the X-ray photoelectron spectrum (XPS) of the hollow triangular nickel-cobalt hydroxide nanosheets prepared in Example 1, and Figures a and b correspond to the spectra of the two elements Ni and Co, respectively;
[0017] Figure 4 The materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were 2mVs -1 Polarization curves in 1M KOH solution at a scan rate of ;
[0018] Figure 5 This is a stability test curve of the hollow triangular nickel-cobalt hydroxide nanosheet prepared in Example 1 maintained at a constant voltage for 10 hours;
[0019] Figure 6 This is the X-ray diffraction spectrum (XRD) of the hollow triangular nickel-cobalt hydroxide nanosheets prepared in Example 1. DETAILED DESCRIPTION
[0020] The present invention will be further described below by preferred embodiments:
[0021] Example 1: Preparation method of hollow triangular nickel-cobalt hydroxide nanosheets Example 1
[0022] 1314 mg of 2-methylimidazole (C4H6N2) and 582 mg of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) were dissolved in 40 mL of ultrapure water, respectively. The two solutions were mixed and then added with clean nickel foam. The mixture was stirred for 3 hours to obtain Co-ZIF nanosheets (the loading amount of Co-ZIF nanosheets on nickel foam in this step was 7 mg·cm -2 , that is, 7 mg Co-ZIF nanosheets are loaded on every square centimeter of nickel foam surface).
[0023] The obtained Co-ZIF nanosheets supported on nickel foam were mixed with nickel nitrate hexahydrate (Ni(NO3)2·6H2O) in ethanol, where the molar ratio of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) used in the previous step to nickel nitrate hexahydrate (Ni(NO3)2·6H2O) used in this step was 1:8. The mixture was stirred at 27°C for 1 hour to finally obtain hollow triangular nickel cobalt hydroxide nanosheet materials supported on nickel foam.
[0024] The hollow triangular nickel-cobalt hydroxide nanosheet material loaded on nickel foam obtained in Example 1 was subjected to SEM, TEM, XPS and XRD spectra, and the Figure 1 , 2 , 3, and 6. Figure 1 It can be seen that the morphology of the hollow nickel-cobalt hydroxide nanosheets is a triangular hollow nanosheet composed of nanosheets. During the OER test, the hollow structure can increase the contact area between the electrolyte and the electrocatalytic material, which is beneficial to the flow of the electrolyte and thus enhances the electrocatalytic activity of the catalyst. Figure 2 It can be seen that the surface of the triangular hollow nanosheet is composed of many tiny interlaced nanosheets. The above results confirm that the material obtained in Example 1 is a hollow nickel-cobalt hydroxide nanosheet. Figure 3 From the surface valence state analysis, it can be seen that Figure a is the XPS spectrum of Ni, and the peaks at 855.9 and 873.7 eV are the oxidized Ni 2+ Figure b is the XPS spectrum of Co. The peaks at 781.6 and 796.9 eV are Co 2+ .Depend on Figure 6 The XRD pattern shows that the material obtained in Example 1 matches the nickel cobalt hydroxide with the card number JCPDS No. 33-0429, corresponding to the (003), (006), (012), (015), (018), (110) and (113) crystal planes (which can be proved to be cobalt nickel hydroxide). The above results confirm that the hollow triangular nickel cobalt hydroxide nanosheet material obtained in Example 1 was successfully prepared, and the hollow structure is conducive to charge transfer and transmission in the OER process.
[0025] Example 2: Preparation method of hollow triangular nickel-cobalt hydroxide nanosheets Example 2
[0026] 1314 mg of 2-methylimidazole (C4H6N2) and 476 mg of cobalt chloride hexahydrate (CoCl2·6H2O) were dissolved in 45 mL of ultrapure water, the two solutions were mixed, clean nickel foam was added, and stirring was continued for 6 hours to obtain Co-ZIF nanosheets loaded on nickel foam (the loading amount of Co-ZIF nanosheets in this step was 10 mg·cm -2 ).
[0027] The obtained Co-ZIF nanosheets supported on nickel foam were mixed with nickel sulfate (NiSO4) in ethanol, the molar ratio of cobalt chloride hexahydrate (CoCl2·6H2O) used in the previous step to nickel sulfate (NiSO4) was 1:1, and the temperature was kept at 80°C for 3 hours to finally obtain hollow triangular nickel cobalt hydroxide nanosheet materials.
[0028] Example 3: Preparation method of hollow triangular nickel-cobalt hydroxide nanosheets Example 3
[0029] 1314 mg of 2-methylimidazole (C4H6N2) and 498 mg of cobalt acetate tetrahydrate (C4H6CoO4·4H2O) were dissolved in 50 mL of ultrapure water, the two solutions were mixed, clean nickel foam was added, and stirring was continued for 2 hours to obtain Co-ZIF nanosheets (the loading amount of Co-ZIF nanosheets in this step was 8 mg·cm -2 ).
[0030] The obtained Co-ZIF nanosheets supported on nickel foam were mixed with nickel chloride (NiCl2) in ethanol, the molar ratio of cobalt acetate tetrahydrate (C4H6CoO4·4H2O) used in the previous step to nickel chloride (NiCl2) was 1:10, and the temperature was kept at 60°C for 7 hours to finally obtain hollow triangular nickel cobalt hydroxide nanosheet materials.
[0031] Example 4: Preparation method of hollow triangular nickel-cobalt hydroxide nanosheets Example 4
[0032] 1314 mg of 2-methylimidazole (C4H6N2) and 366 mg of cobalt nitrate (Co(NO3)2) were dissolved in 60 mL of ultrapure water, respectively. The two solutions were mixed and then clean nickel foam was added. The mixture was stirred for 4 hours to obtain Co-ZIF nanosheets (the loading amount of Co-ZIF nanosheets in this step was 5 mg cm -2 ).
[0033] The obtained Co-ZIF nanosheets supported on nickel foam were mixed with nickel nitrate (Ni(NO3)2) in ethanol. The molar ratio of cobalt nitrate (Co(NO3)2) to nickel nitrate (Ni(NO3)2) used in the previous step was 1:4. The temperature was kept at 40°C for 10 hours to finally obtain hollow triangular nickel cobalt hydroxide nanosheet materials.
[0034] The hollow triangular nickel-cobalt hydroxide nanosheets prepared in Examples 2, 3 and 4 were subjected to SEM, TEM, XRD and XPS spectra, respectively, and the conclusions were basically the same as those in Example 1. The enlarged experiments of the above four examples showed that multiple products could be prepared with comparable performance.
[0035] Example 5 Electrocatalytic Performance Test
[0036] Taking Example 1 as an example, an electrocatalytic performance test was conducted, and the catalytic performance was compared with the following comparative examples.
[0037] Comparative Example 1: Example of ion exchange without using nickel salt
[0038] (a) 1314 mg of 2-methylimidazole (C4H6N2) and 582 mg of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) were dissolved in 40 mL of ultrapure water, respectively. After the two solutions were mixed, clean nickel foam was added and stirred for 3 h to obtain Co-ZIF nanosheets.
[0039] (b) The obtained Co-ZIF nanosheets were placed in ethanol and stirred at 27°C for 1 hour to finally obtain cobalt nanosheet materials.
[0040] Comparative Example 2:
[0041] Commercially available ruthenium dioxide was purchased without treatment.
[0042] Comparative Example 3:
[0043] The nickel foam was ultrasonically cleaned for 20 minutes using acetone, ethanol, 3M hydrochloric acid and ultrapure water in sequence, and then dried at room temperature for later use (in the electrochemical test, the effective area of the nickel foam was 1*1 cm).
[0044] Test process:
[0045] 10 mg of the material of Comparative Example 2 was dispersed in a mixed solution of 980 μl of ethanol and 20 μl of Nafion to prepare a catalyst slurry; then 200 μl of the catalyst slurry was dropped on a clean nickel foam (effective area of 1*1 cm), and after drying, the corresponding working electrode was made, and an electrocatalytic comparison test was carried out together with the electrodes of Example 1 and Comparative Examples 1 and 3.
[0046] In the electrocatalytic test, platinum and Hg / HgO were used as the counter electrode and reference electrode respectively; the potential was referenced to the reversible hydrogen electrode (RHE): E RHE =E Hg / HgO + 0.098 + 0.059 × pH (1M KOH solution). The overpotential (η) was calculated according to the following equation: η = E RHE -1.23V. at 2mV·s -1 Linear sweep voltammetry (LSV) was recorded in 1 M KOH solution at a scan rate of 1.5 % to obtain polarization curves, see Figure 4 , Figure 4 The electrode potential data were 90% iR compensated. The stability test was performed at constant potential for 10 hours, see Figure 5 .
[0047] Depend on Figure 4 It can be seen that the electrocatalyst of Example 1 can significantly reduce the overpotential when applied to the oxygen evolution reaction in an alkaline environment (relative to the cobalt nanosheets of Comparative Example 1, the commercial ruthenium dioxide of Comparative Example 2, and the blank nickel foam of Comparative Example 3). Compared with Comparative Example 3, the current density of the electrocatalyst of Example 1 is significantly increased, indicating that the high activity comes from the electrocatalyst itself rather than the substrate of the working electrode (blank nickel foam). Compared with Comparative Example 1, the electrocatalyst of Example 1 exhibits a huge activity advantage, indicating that its activity mainly comes from the doping and hollow structure of nickel. Compared with Comparative Example 2, the electrocatalyst of Example 1 has a higher current density and a lower potential, indicating that the catalyst has the potential to replace commercial ruthenium dioxide. In addition, the electrocatalyst of Example 1 has a high current density and a low potential at 20 and 50 mA·cm -2 The overpotential is only 285 and 313 mV at the current density, showing excellent electrocatalytic oxygen production activity. Figure 5 It can be seen that the prepared electrocatalyst has good stability in alkaline electrolyte and is stable for 10 hours under constant voltage, indicating that the hollow triangular nickel cobalt hydroxide nanosheets have strong structural stability. The hollow nanosheets can effectively prevent catalytic aggregation, so that it can still maintain the high activity of its catalytic sites during a long reaction process. The high activity of electrocatalytic oxygen production mainly comes from the large active area of the hollow structure of the NiCo hydroxide triangular nanosheets, the abundant active sites and the synergistic effect between electrons. The preparation method of this catalyst is expected to be extended to the synthesis of other metal hydroxide nanosheets, thus having broad application prospects in the field of energy storage and conversion.
[0048] The above embodiments are merely illustrative of the concept and implementation of the present invention, and are not intended to limit the concept and implementation of the present invention. Under the concept of the present invention, technical solutions that have not been substantially changed are still within the scope of protection.
Claims
1. An application of nickel cobalt hydroxide nanosheets, the application being to catalyze the oxygen evolution reaction of water electrolysis in an alkaline environment, Features Nickel cobalt hydroxide nanosheets were prepared by the following method: (a) 2-methylimidazole and cobalt salt are dissolved in water to obtain solutions, the two solutions are mixed and added into nickel foam, and then taken out after stirring to obtain Co-ZIF nanosheets supported on nickel foam, wherein the loading amount of the Co-ZIF nanosheets on the nickel foam is 5-10 mg·cm -2 ; (b) The Co-ZIF nanosheets supported on nickel foam and nickel salt are mixed in ethanol, stirred at a constant temperature of 20-80° C. for 1-10 hours, and taken out to obtain nickel cobalt hydroxide nanosheets supported on nickel foam, wherein the molar ratio of the cobalt salt to the nickel salt is 1:1-10.
2. The use of the nickel cobalt hydroxide nanosheets as claimed in claim 1, It is characterized in that The cobalt salt is selected from Co(NO 3 ) 2 6H 2 O、CoCl 2 6H 2 O、Co(NO 3 ) 2 or C 4 H 6 CoO 4 ·4H 2 O; the nickel salt is selected from Ni(NO 3 ) 2 6H 2 O.Ni(NO 3 ) 2 、NiSO 4 or NiCl 2 .
3. Use of the nickel cobalt hydroxide nanosheets as claimed in claim 1, It is characterized in that The loading amount of the Co-ZIF nanosheets on nickel foam is 6-7 mg cm -2 ; The molar ratio of the cobalt salt to the nickel salt is 1:7~8.
4. The use of the nickel cobalt hydroxide nanosheets as claimed in claim 1, It is characterized in that The Co-ZIF nanosheets supported on the nickel foam are obtained after continuous stirring for 3 hours in the step (a); the Co-ZIF nanosheets supported on the nickel foam and nickel salt are mixed in ethanol, and stirred at a constant temperature of 27° C. for 1 to 2 hours to obtain the nickel cobalt hydroxide nanosheets supported on the nickel foam.
